THE CORRELATION OF KNOWLEDGE AND ATTITUDES TOWARDS THE PRACTICE OF SCABIES AMONG STUDENTS IN ISLAMIC BOARDING SCHOOLS IN BONDOWOSO - Siti Riskika; Alwan Revai; Hanan Alawiyah Al-Joefrie (UNEJ e-Proceeding, 2020)
Background: Scabies is a contagious mite infestation of the skin, endemic in tropiand subtropical countries. The transmission of scabies through direct and prolonged contact and sharing clothes and neglected disease for this era. Purpose: The aims of this study to determine the relationship knowledge and attitudes with practice to prevent scabies in Islamic boarding school. Methods: This study in an islamic boarding school in Bondowoso, the participants are the students of grade two and three junior high school with total sampling technique, the instruments modified from TPB questionnaires and used a cross-sectional with a chi-square test. Results: The chi-square test showed that there is a correlation between knowledge and practice with p-value 0,042 (< 0,05) and the results of the correlation between attitudes and practice with p-value 0,026 (< 0,05), the student’s knowledge of scabies and personal and environmental hygiene, it can enhance the practice to prevent scabies. Good knowledge and positive attitude can make scabies prevention practice become positive. Conclusion: The better student’s knowledge and attitudes in preventing scabies, the better the practical efforts in preventing scabies will be. Keywords: Scabies, students, knowledge, attitude, practice